2007
DOI: 10.1074/jbc.m606764200
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin Cs Are Key for the Intracellular Survival of the Protozoan Parasite, Toxoplasma gondii

Abstract: Cysteine proteases play key roles in apicomplexan invasion, organellar biogenesis, and intracellular survival. We have now characterized five genes encoding papain family cathepsins from Toxoplasma gondii, including three cathepsin Cs, one cathepsin B, and one cathepsin L. Unlike endopeptidases cathepsin B and L, T. gondii cathepsin Cs are exopeptidases and remove dipeptides from unblocked N-terminal substrates of proteins or peptides. TgCPC1 was the most highly expressed cathepsin mRNA in tachyzoites (by real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 23 publications
1
82
0
Order By: Relevance
“…Targeted deletion of a gene family member in T. gondii can lead to upregulation of another member of the gene family (46). To determine whether deletion of TgPI1 resulted in compensatory upregulation of other T. gondii genes, including those encoding other serine protease inhibitors, we performed genome-wide expression profiling using a custom T. gondii Affymetrix microarray (Toxodb.org) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted deletion of a gene family member in T. gondii can lead to upregulation of another member of the gene family (46). To determine whether deletion of TgPI1 resulted in compensatory upregulation of other T. gondii genes, including those encoding other serine protease inhibitors, we performed genome-wide expression profiling using a custom T. gondii Affymetrix microarray (Toxodb.org) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cathepsin proteases act clasically as lysosomal hydrolases that digest endogenous and exogenous endocytosed polypeptides [706] . They function in microneme and rhoptry protein maturation, host cell invasion, replication, and nutrient acquisition [707,708] . Que et al [705] showed that the TgCatB, toxopain-1, was localized to rhoptries (secretory organelles required for parasite invasion into cells), and was critical for parasite invasion and rhoptry protein processing.…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…Cathepsins are critical to the parasite growth and differentiation [707] . T. gondii cathepsins were required for peptide degradation in the parasitophorous vacuole (PV), as the degradation of the marker protein, E. coli β-lactamase, secreted into the PV of transgenic tachyzoites was completely inhibited by the CatC inhibitor [707] .…”
Section: T Gondii Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin C family members, including the Toxoplasma gondii enzyme most closely related to Cth4p, are comprised of 5 recognized domains: a signal peptide, an exclusion domain, a internal proregion, and finally a catalytic heavy and light chain (Fig. 12A) (48). In the comparatively well-studied mammalian cathepsin C, it is known that the first three domains are removed in a maturation process, to generate a catalytically active heavyϩlight chain (HL) species (49).…”
Section: Figmentioning
confidence: 99%